Short stature in children of Karapotó ethnic background, São Sebastião, Alagoas, Brazil - Samara Bomfim Gomes Campos; Risia Cristina Egito de Menezes; Maria Alice Araújo Oliveira; Danielle Alice Vieira da Silva; Giovana Longo-Silva; Juliana Souza Oliveira; Leiko Asakura; Emília Chagas Costa; Vanessa Sá Leal (Sociedade de Pediatria de São Paulo, 2016)
Abstract Objective: To describe the prevalence of short stature among children of Karapotó ethnic background. Methods: Cross-sectional, population-based study that included children between 6 and 59 months of age from the Plak-Ô native village and the Terra Nova settlement, São Sebastião, Alagoas, carried out between 2008 and 2009. Short stature was evaluated by the Height/Ageindex, using as cutoff z score≤−2. The prevalence of short stature was determined by compa-ring simple and relative frequencies. The population growth curves were compared to the WHO reference curves. Data analysis included the outcome variable: Height/Age and the predictor variables: place of residence, gender, age, anemia, birth weight, family income, maternal literacy. The chi-square test was used to compare the categorical variables, where as the chi-square test with Yates correction was used for dichotomous variables, considering as statistically significant p-values≤0.05. Results: The prevalence of short stature was 15.6% for children from the Terra Nova settlement and 9.1% for those from Plak-Ô native village. The prevalence of short stature among the Karapotó ethnicity was 13.4%. The variables: maternal literacy, family income and low birth weight were statistically associated with short stature. Conclusions: The observed short stature prevalence rates are significant, being characterized as a public health problem. Among the associated factors, the following are noteworthy: unfavorable conditions of maternal literacy, family income and low birth weight. The planning of strategies to reverse the situation must take such factors into consideration.